Implementation of Islamic Religious Education for Children with Special Needs in Tolitoli Regency - Lutfi; Askar; Rusli Takunas; Andi Anirah (Journal of Contemporary Islamic Education, 2025)
Islamic Religious Education for children with special needs (ABK) is both a challenge and an urgent need amidst efforts to realize inclusive education in Indonesia. This study aims to analyze the implementation of Islamic Religious Education in inclusive schools and madrasahs that accept children with special needs in Tolitoli Regency, Central Sulawesi. The study used a qualitative approach with observation, interviews, and documentation methods with Islamic Religious Education teachers, school or madrasah principals, and parents of students with special needs. The results show that the implementation of Islamic Religious Education still faces obstacles, both in terms of the availability of teachers with special pedagogical competencies, limited adaptive learning media, and a lack of supporting infrastructure. However, there are local strategies developed by teachers, such as individual approaches, practice-based learning methods, and the use of visual media to facilitate the understanding of religious concepts. This study emphasizes the importance of strengthening the capacity of Islamic Religious Education teachers through inclusive education training, collaboration with parents, and support from local government policies in providing an adaptive curriculum. Thus, the implementation of Islamic Religious Education for children with special needs (ABK) in Tolitoli Regency can become a learning model based on local wisdom that is humanistic, inclusive, and equitable.